Jan Dibbets. - Van Abbemuseum, Eindhoven; ARC Musée d'Art Moderne de la Ville de Paris; Kunsthalle Bern, Bern (Eindhoven : Van Abbemuseum Eindhoven, 1980)
This book is the catalogue of all the photographic works of Jan Dibbets from 1967 to 1980.
biog., ind. tent [1 p.], bibliog. [1 p.]
Engels
Jan Dibbets. Van Abbemuseum Eindhoven February 15 - March 30, 1980 / ARC Musée d'Art Moderne de la Ville de Paris April 16 - June 1, 1980 / Kunsthalle Bern, June 13 - July 27, 1980
boek
Keywords: Dibbets, Jan